STRATEGI PENCEGAHAN KEBAKARAN LAHAN GAMBUT PADA KESATUAN HIDROLOGIS GAMBUT SUNGAI AMBAWANG-SUNGAI KUBU PROVINSI KALIMANTAN BARAT - rezza permana kusuma juliarsih; U. Edi Suryadi; Novira Kusrini (JURNAL BORNEO AKCAYA, 2022)
The phenomenon of peatland fires in Kubu Raya Regency occurs continuously every year. The Ambawang River-Kubu River KHG is one of the BRG priority target areas in the early stages. Hotspots that fluctuated from 2009 to 2019 indicate that all efforts to prevent and control peatland fires in the Kubu Raya Regency area are still not effective. It is necessary to identify the activities that have been carried out by the community and related parties (stakeholders), internal and external factors, and formulate alternative strategies for preventing peatland fires according to conditions in the Ambawang River–Sungai Kubu KHG area. Observations were used to collect field conditions at the research site. SWOT analysis is used to determine the best strategy that farmers should take to prevent peatland fires. The absence of dams drilled wells and canal blocking, lack of fire extinguishers, poor early warning system, infrequent socialization, and appeals for land fire prevention by the relevant agencies and the newly formed MPA. Prevention of land fires is in the WT strategy, where the recommended strategies are to survive by continuing to do corn farming, conducting various simple experiments to find better ways to harvest corn without burning the land, forming farmer groups as a means of deliberation and exchange of ideas, increasing the role of active farmers in seeking various information related to agriculture and land fire prevention.